ANALISIS KELAYAKAN USAHA BUDIDAYA UDANG VANAME POLA TRADISIONAL PLUS DI KECAMATAN SAMATURU KABUPATEN KOLAKA - Imelda Isamu; Idrus Salam; Lukman Yunus (Jurnal Sosio Agribisnis, 2018)
Vaname shrimp is one of the aquaculture commodities which is the mainstay of export commodities of the government in improving non-oil and gas foreign exchange. This research aims to: analyze the income of shrimp farming business of Vanamee traditional pattern plus in Samaturu Sub-district of Kolaka Regency, and analyze the financial feasibility of shrimp farming business of Vanamee traditional pattern plus in Samaturu Sub-district of Kolaka. Respondents in this research are Vanamee shrimp farmers located in District Samaturu Kolaka District, with 34 farmers. The analysis used in this study is income analysis,  R/C-ratio analysis, payback period (PP) analysis and return of invesment (ROI) analysis. Result of research indicate that: Vanamee shrimp farming income of traditional pattern plus in Samaturu Sub-district of Kolaka Regency is Rp 48,173.451 per hectare per year, and Vanamee shrimp farming business in traditional pattern plus in Samaturu District Kolaka Regency is financially. Therefore, the role of government and private sector is needed to support the provision of cultivation facilities and infrastructure.Keywords: income; Vanamee shrimp; farming; feasibility